Ciudades de los Andes: la calle como memoria y como umbral - Eduardo Kingman Garcés; Erika Bedón C. (Confluenze, 2025)
The key objective of this article is to reflect upon the Rocafuerte Street and the Streets’ network neighboring the old town in Quito, which has been supporting a rich ensemble of social and cultural relationships that are characteristic features of the Andean region. This space is not only a popular trade zone open to negotiation among pairs and not pairs, but also, it constitutes a space of encounters and relationships with its own cultural practices. It is, on the other hand, a border space or threshold between the patrimonialized and the non-patrimonialized part of the old town.